Child Recruitment and Use during Armed Conflicts by Muslims between International Law and Islamic Law - Khdir, Rebaz R. (European Scientific Journal, ESJ, 2022)
Child recruitment is an ancient military concept but a modern legal term. The term is defined as a war crime and includes the acts of conscription, enrolment or use of children below the age of 15 during armed conflict. According to the 2018 report of the UN Secretary General, most of the violations documented against children during armed conflicts, in 2017, were perpetrated by Muslims and the majority of the violations were the cases of military recruitment and use. Meanwhile, Islam guarantees the human rights of children and safeguards their protection from military involvement. The Islamic primary and secondary sources entail considerable and substantial evidence according to which people under the age of puberty are exempted from and not allowed to participate in battle. Yet, Muslims have often recruited and used children in deadly political and sectarian conflicts, and Islamic courts have never prosecuted anyone for such a practice. This article, based on comparative and descriptive analysis, argues that the Muslim states and groups that recruit and use children during armed conflicts are in violation of international law and Islamic law. Islamic law works in tandem with international law in the prohibition and criminalization of child recruitment and use.